The Transcriptomic Signature of Tigecycline in Acinetobacter baumannii - Li, Liping; Hassan, Karl A.; Tetu, Sasha G.; Naidu, Varsha; Pokhrel, Alaska; Cain, Amy K.; Paulsen, Ian T. (Frontiers in Microbiology, 2020)
Tigecycline, a protein translation inhibitor, is a treatment of last resort for infections caused by the opportunistic multidrug resistant (MDR) human pathogen Acinetobacter baumannii. However, strains resistant to tigecycline were reported not long after its clinical introduction. Translation inhibitor antibiotics perturb ribosome function and induce the reduction of (p)ppGpp, an alarmone involved in the stringent response and negatively modulates ribosome production. Through RNA sequencing, this study revealed that the ability of A. baumannii to survive tigecycline treatment at a sub-inhibitory concentration may be directly related to (p)ppGpp. Our results indicated that the drug-induced reduction of the (p)ppGpp level promoted the production but diminished the degradation of ribosomes, to counteract the translational inhibition effect by tigecycline. The reduction of (p)ppGpp also led to a decrease of transcription coupled nucleotide excision repair which likely increases the chances of development of tigecycline resistant mutants. The most highly upregulated gene, involving in RNA repair, is either a direct tigecycline stress response or is in response to the transcription de-repression of a toxin-antitoxin system which can be induce by translational inhibition. The most down-regulated genes encode two β-lactamases, which is a possible by-product of tigecycline-induced reduction in transcription of genes associated with cell division. This transcriptomics study provides a global genetic view of why A. baumannii is able to rapidly develop tigecycline resistance.